2017
DOI: 10.1103/physrevlett.118.067204
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-Induced Revival of the Bose-Einstein Condensation inNi(Cl1xBrx

Abstract: Building on recent NMR experiments [A. Orlova et al., Phys. Rev. Lett. 118, 067203 (2017)], we theoretically investigate the high magnetic field regime of the disordered quasi-one-dimensional S = 1 antiferromagnetic material Ni(Cl1−xBrx)2-4SC(NH2)2. The interplay between disorder, chemically controlled by Br-doping, interactions, and the external magnetic field, leads to a very rich phase diagram. Beyond the well-known antiferromagnetically ordered regime, analog of a Bose condensate of magnons, which disappea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 64 publications
(92 reference statements)
5
28
0
Order By: Relevance
“…Above H c2 , many-body physics is thus controlled by the effective pairwise interaction between such localized impurity states. This sheds a new light on the BG physics expected in this system above H c2 [13]; while a BG regime implies the absence of any long-range order down to T = 0, in the related theoretical work [23] it is shown that around H * the impurity states order at low T , thereby profoundly changing the phase diagram.The present investigation of DTNX is based on previous NMR work on DTN samples [24,25], enabling prearXiv:1607.02360v3 [cond-mat.str-el] …”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Above H c2 , many-body physics is thus controlled by the effective pairwise interaction between such localized impurity states. This sheds a new light on the BG physics expected in this system above H c2 [13]; while a BG regime implies the absence of any long-range order down to T = 0, in the related theoretical work [23] it is shown that around H * the impurity states order at low T , thereby profoundly changing the phase diagram.The present investigation of DTNX is based on previous NMR work on DTN samples [24,25], enabling prearXiv:1607.02360v3 [cond-mat.str-el] …”
mentioning
confidence: 74%
“…Including quantum dynamics provides crucial information on the (de)localization of the spin around the impurities [23]. For a single impurity, this can be studied both analytically or numerically by exact diagonalization (ED).…”
Section: −1mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, interactions are strongly modified, especially J c for which the twohalide bond is the primary superexchange mediator [17]. Recent NMR [25] and theoretical [26] studies suggest that these modification of the Hamiltonian (1) parameters are very local.…”
Section: A Dtnx: a Short Introductionmentioning
confidence: 99%
“…The false color plot shows scattering intensity versus energy transfer ω and momentum transfer along Q = (0.5, 0.5, l) reciprocal space rod, the antiferromagnetic zone center (0.5, 0.5, 0.5) being the global dispersion minimum where the gap is observed directly. The Br-substituted material Ni(Cl 1−x Br x ) 2 ·4SC(NH 2 ) 2 has attracted a great deal of interest in the context of effects of disorder on the field-induced quantum phase transitions [12,15,16] and magnetic excitations [11,17]. However, as was clearly shown by neutron spectroscopy studies, the most obvious effect of Br substitution can be understood simply in terms of its influence on average exchange and anisotropy constants [11].…”
mentioning
confidence: 99%